Peculiarities Of Investigating Negligent Severe Or Moderately Severe Bodily Harm At The Initial Stage - Penzieva, Kateryna (Archives of Criminology and Forensic Sciences, 2023)
One of the important stages in the development of a separate sub-type methodology for investigating negligent severe or moderately severe bodily harm is the determination of the specifics of the initiation of criminal proceedings based on this fact and circumstances to be established during investigation of the specified criminal offense. Conducting a study of this issue will serve to eliminate the gap in forensic science, since currently the indicated methodology has not yet been developed. The Article purpose is to provide scientifically-based criminological recommendations regarding the specifics of initiating a pre-trial investigation into the infliction of negligent severe or moderately severe bodily harm. This includes outlining a set of investigative (search) and other procedural actions based on various typical investigative situations, with a focus on determining circumstances to be established during investigation of this crime. An analysis of investigative and judicial practices was conducted to study the methods used in investigating specific types of criminal offenses, peculiarities of initiating pre-trial investigations for the specified criminal offense. As a result, information sources about the committed crime have been determined. The tasks that must be solved by a person conducting a pre-trial investigation at its initial stage are formulated. The most typical investigative situations at the initial stage of investigating negligent severe or moderately severe bodily harm have been determined, taking into account informational, psychological, tactical, and procedural factors affecting their formation. The main investigative situations occurring during investigation of the specified type of crime are: - Investigative Situation No. 1. At the time of opening a criminal proceeding, there is information about a person’s identity and his/her whereabouts; the suspect has been apprehended. - Investigative situation No. 2. The offender’s identity is known, but his/ her whereabouts has not been established. - Investigative situation No. 3. The suspect’s identity and his/her whereabouts are unknown. Depending on each specific investigative situation, recommendations are provided regarding the optimal conduct of a pre-trial investigation at this stage, namely, a list of tasks, investigative (search) and other procedural actions. The list of circumstances to be established during investigation of criminal offenses based on the fact of negligent infliction of severe or moderately severe bodily harm is defined.